The implementation of the milk al-manfaah concept in Malaysia: Reference to the group settlement area land act (1960) - Mohamad, Zulkifli; Noor, Ruzman Md; Tapah, Suwaid; Hassan, Wan Zulkifli Wan; Zainal, Khalim; Muslim, Nazri; Umar, Azizi; Basir, Aminuddin; Yusoff, Abdul Salam; Yunos, Nasruddin; Alias, Jamsari (IAEME Publication, 2018)
This article will discuss the success of the joint-venture between the Federal Goevrnment and the State Government in their effort to develop the agricultural land through the concept of’milk al-manfaah’. Therefore, the Group Settlement Land Act (1960) has been formulated in the Parliament. Through this Act, every settler is granted 10 acres of farm lands by means of the al-manfaah milk. The benefit ownership concept has been practised widely in the law history of the Islamic land by the Uthmaniyyah government named as the miri land. The same concept has been of practice in Egypt as well as several other Islamic countries. Based on the land Federal Constitution, it is located under the jurisdiction of the state government, whereas FELDA serves as a government agency. Through the 1960 Land Act, the Federal Government is permitted to perform land duties before the ownership is issued by the State Government. Based on the milk al-manfaah concept, FELDA has successfully developed 447,578 hectares of land in Malaysia.